(untitled) (Economic studies journal, 2023)
The study aimed to demonstrate the impact of financial safety indicators (bank size, capital adequacy, liquidity, return on equity, debt-to-equity ratio) on the financial stability of Libyan commercial banks. The study sample contained only two commercial banks among the private banks that met the conditions placed in the study to select the sample, which are the Trade and Development Bank and the United Bank for Trade and Investment during the time period (2012-2018), and to achieve the objectives of the study, the hypotheses were formulated and tested using the multiple regression model through the appropriate statistical indicators for the study, and the study concluded that the indicators of financial soundness have an impact on financial stability.